2001
DOI: 10.2166/wst.2001.0850
|View full text |Cite
|
Sign up to set email alerts
|

Residential subsurface flow treatment wetlands in northern Minnesota

Abstract: Approximately 30% of Minnesotans use on-site systems (approximately 500,000 residences) and >50% are failing or non-compliant with regulations due to restrictive soils and site conditions. Many sites occur near lakes and streams creating health hazards and deteriorating water quality. SSF CWs have been evaluated year-round at two northern sites since 1995. The NERCC CWs simulate single homes and the Grand Lake demonstration CW treats STE from a cluster of 9 lakeshore homes. Systems were generally able to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Further details about the treatment systems and their seasonal performance for removing the model pathogen, Salmonella choleraesuis, may be found in Pundsack (2000) and Pundsack et al (2001). Details regarding the overall design, construction, operation and performance of the treatment systems may be found in McCarthy et al (1997McCarthy et al ( , 1998McCarthy et al ( , 1999 and Axler et al (1999Axler et al ( , 2001. (Hicks et al 1992;DeLong 1993;Amann et al 1995;Pommepuy et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the treatment systems and their seasonal performance for removing the model pathogen, Salmonella choleraesuis, may be found in Pundsack (2000) and Pundsack et al (2001). Details regarding the overall design, construction, operation and performance of the treatment systems may be found in McCarthy et al (1997McCarthy et al ( , 1998McCarthy et al ( , 1999 and Axler et al (1999Axler et al ( , 2001. (Hicks et al 1992;DeLong 1993;Amann et al 1995;Pommepuy et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…McCarthy et al (1997,1998,1999) and Axler et al (2001) showed significant decreases in the reduction of nitrogen, phosphorus and BOD 5 in winter relative to summer.…”
Section: Introductionmentioning
confidence: 95%
“…These viruses, including polio virus, hepatitis, norwalk virus, rotavirus and others, can easily reach water sources and become a serious human health concern. This problem is accentuated in communities in northern Minnesota due to lack of centralized wastewater treatment, small lot size, close proximity to water sources, poor or thin soils, and a long, severe winter during which performance may decrease dramatically (Crosby et al 1998;McCarthy et al 1998McCarthy et al , 1999Axler et al 2001;Henneck et al 2001;Pundsack et al 2001;Kadlec et al 2003). In Minnesota, nearly 30% of the population is dependent on onsite treatment systems with more than 500,000 individual onsite treatment systems in use state-wide (MPCA 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations